Sirkulasi Keputusan Dan Dampak Menjadi Pekerja Migran: Studi Etnografi Proses Pengambilan Keputusan Menjadi Pekerja Migran Indonesia - Citra Nur Hamidah (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2018)
Limited employment opportunities in Indonesia encourage Indonesians to seek employment abroad and choose to become migrant workers. There are two migration processes; procedural migration and unprocedural migration. In this study, I would like to show the global labor migration reviewed from the local level of the migrant worker’s village. My focus to explore the decision-making process of migrant workers created in thehousehold and the village. I argue that ethnography approach casting light on social and cultural contexts for thought, reason, and action can explain how choices are framed and constituted. I used an ethnography approach to explain the decision-making process and to understand the daily life of migrant workers in the village and household units. I conducted fieldwork (live in) in Kebondalem Village, Banyuwangi for 3 months.In the context of migrant workers, I offered a new concept to explore the decision-making process, that is 'long distance decision making process'. The process of decision making into migrant workers is never completed and always formed through daily activities, even households negotiated.